The role of muscle tissue in the pathogenesis of chronic heart failure — the potential of exposure (FORMA study) - T. A. Lelyavina; M. Yu. Sitnikova; V. L. Galenko; P. S. Kozlov; M. A. Bortsova; E. A. Demchenko; O. S. Ganenko; A. S. Golovkin; A. A. Kostareva; R. I. Dmitrieva (Российский кардиологический журнал, 2019)
Aim. To determine whether the skeletal muscle of patients with chronic heart failure (CHF) retains the ability to regenerate and grow; to compare the effectiveness of long aerobic trainings, calculated by an individualized method, and conventionally calculated trainings (VO2peak values), in relation to the severity of heart failure, exercise tolerance (ET), and ergoreflex activity (ERGO).Material and methods. The study included 297 patients with stable III functional class (FC) CHF, receiving optimal therapy. The presence of heart failure was found in all patients at least 6 months before the start of the study (age — 18-65 years, body mass index (BMI) — 19-28 kg/height, m2. Initially, the study performed a cardiorespiratory test (CRT) with an assessment of gas composition, acid-base balance of the blood and ERGO activity. Patients were randomized into 2 groups: experimental (EG) and control (CG). For EG, based on the determination of the lactate threshold (LT), after 1 and 3 months the CRT was repeated and the training walking mode was dynamically recounted according to the new LT level. For CG, the training walking mode was calculated based on the VO2peak values. All patients trained for 6 months. At the end of the training, diagnostic CRT was performed, and the activity of EGO was evaluated. Eleven patients with CHF and 3 healthy donors before the start of the training underwent a biopsy of the gastrocnemius muscle.Results. It was shown that the potential for muscle differentiation of satellite skeletal muscle precursor cells obtained from patients with CHF with a reduced ejection fraction (HFrEF) does not differ in vitro from the potential of satellite cells of healthy donors. After 6 months of training, the severity of CHF decreased to FC II in 75% of EG patients, and among CG patients — in 44%; the main indicators of the stages of compensatory mechanisms activation during physical exertion (VO2LT and VO2peak) in EG increased more than in the CG (10,8±0,4, 18,7±0,7 ml/min/kg and 9,5±0,8, 15,3±0,9 ml/min/kg, with p1<0,01, p2<0,05, p3<0,01, respectively). Conclusion. In vitro, the potential for muscle differentiation, regeneration and growth of satellite skeletal muscle precursor cells obtained from patients with HFrEF does not differ from the potential of satellite cells of healthy donors. Aerobic training in patients with III FC chronic heart failure calculated by definition of LT, relating to safety is not worse than the results calculated by the level of VO2peak. Aerobic training in patients with III FC chronic heart failure calculated by definition of LT, compared with the usual mode of training walking, significantly reduce the activity of ergoreflex, increase ET, reduce the severity of CHF. In patients with III FC CHF, training walking for more than 1,5 hours/day determined by the level of LT, contributes to the development of physiological reverse myocardial remodeling to a greater extent than aerobic training calculated by the conventional method.